Industrial Training (III) - Patankar, P. R. (Journal of Engineering Education Transformations, 1995)
In part I of this article (Vol. VIII No.2 Oct-Dec 1994), the objectives of industrial training and students’ role during training were discussed. Part II (Vol. VIII No. 3 Jan-March 1995) was devoted for giving guide lines for the students regarding what learning situations occur during training and how these should be utilised. In this last part, it is proposed to discuss the placement officer’s functions, skills and attitudes.